Inhibitory effects of local anesthetics on the proteasome and their biological actions - Udin Bahrudin (Nature Portfolio, 2017)
Abstract Local anesthetics (LAs) inhibit endoplasmic reticulum-associated protein degradation, however the mechanisms remain elusive. Here, we show that the clinically used LAs pilsicainide and lidocaine bind directly to the 20S proteasome and inhibit its activity. Molecular dynamic calculation indicated that these LAs were bound to the β5 subunit of the 20S proteasome, and not to the other active subunits, β1 and β2. Consistently, pilsicainide inhibited only chymotrypsin-like activity, whereas it did not inhibit the caspase-like and trypsin-like activities. In addition, we confirmed that the aromatic ring of these LAs was critical for inhibiting the proteasome. These LAs stabilized p53 and suppressed proliferation of p53-positive but not of p53-negative cancer cells.